Molecular Phylogenetic Position of Bacillus sp Bacteria Isolated from Rotifer Culture Medium Based on Fisheries Waste Diet - Wullur, Stenly (Jurnal Ilmiah Platax, 2023)
This study aims to identify and determine the phylogenetic position of two bacterial isolates (F0031 and F0033), isolated from culture media of Rotifer Brachionus plicatilis sp. complex. Genomic DNA of the bacteria was extracted using Qiaprep Miniprep Kit and the 16S rRNA gene was amplified using primer pairs 8F (5'-AGAGTTTGATCCTGGCTCAG-3') and 1492R (5'-ACCTTGTTACGACTT-3'). The sequences were analyzed using Geneious Prime ver. 2020 and bacterial identification was performed using the Basic Local Alignment Tool (BLAST) method.  Phylogenetic analysis was conducted using MEGA X, where the phylogenetic tree was constructed using the Maximum Likelihood method, and evaluated using the Bootstrap method.  Results of this study showed that both bacterial isolates (F0031 and F0033) belong to different genera, namely Bacillus (F0031) and Mesobacillus (F0033). Bacterial isolate F0031 had the closest similarity and was located at the same phylogenetic branch as B. cereus, while isolate F0033 was with M. jeotgali. Keywords: phylogeny, molecular, bacteria, bacillus, mesobaccilus, rotifera, diet. Abstrak Penelitian ini bertujuan untuk mengidentifikasi dan menentukan posisi filogeni dua isolat bakteri (F0031 dan F0033) yang diisolasi dari media kultur rotifer Brachionus plicatili sp. complex.  DNA genom dari isolat bakteri diekstrak menggunakan Kit Qiaprep Miniprep dan gen 16S rRNA diamplifikasi menggunakan pasangan primer 8F (5'-AGAGTTTGATCCTGGCTCAG-3') dan 1492R (5'-ACCTTGTTACGACTT-3').  Hasil sekuens dianalisis menggunakan Sequence scanner ver. 2.0 dan analisis sekuens dilakukan menggunakan Geneious Prime ver. 2020.  Identifikasi isolat bakteri dilakukan dengan metode BLAST (Basic Local Alignment Tools) dan analisis filogenetik dilakukan dengan menggunakan MEGA X, dimana konstruksi filogeni menggunakan metode Maximum Likelihood yang dievaluasi dengan metode Bootstrap. Hasil penelitian menunjukan bahwa kedua isolat bakteri (F0031 dan F0033) merupakan isolat bakteri yang berasal dari genus berbeda, yaitu genus Bacillus (F0031) dan genus Mesobacillus (F0033).  Isolat bakteri F0031 memiliki kesamaan terdekat dan berada pada posisi percabagan filogenetik yang sama dengan B. cereus sedangkan Isolat F0033 dengan M. jeotgali Kata kunci: Filogeni, molekuler, bakteri, bacillus, mesobaccilus, rotifer, pakan